Price and volatility transmission from international to domestic food and fertilizer markets in Central America - Hernandez, Manuel A.; Ceballos, Francisco; Berrospi, Maria Lucia; Perego, Viviana Maria Eugenia; Brown, Melissa; Lopez, Elena Mora (International Food Policy Research Institute, 2024)
Following recent major global shocks that resulted in significant spikes in international food and fertilizer prices, this study analyses the degree of price and volatility transmission from international to selected domestic food and fertilizer markets across seven countries in Central America. We follow a multivariate GARCH approach using monthly data over the period 2000–2022. We find varying results by country and commodities and an overall low to moderate degree of price transmission in levels, but a stronger degree of volatility transmission. We similarly observe some changes in the degree of co-movement between international and domestic price variations over time—depending on the market and commodity under consideration—including after the COVID-19 pandemic and Russia’s invasion of Ukraine as well as after the 2007-2008 food price crisis. Back-of-the-envelope calculations of the effect of an increase in international prices of different food and fertilizers mimicking the peak inflation observed in 2022 reveal small yet non-negligible effects on consumer and producer welfare in Central American countries, which however do not match the magnitude of the food security crisis observed in the region.